Rethinking rural entrepreneurship in the era of globalization: Some observations from Iran - Hassan Shahraki; Ebrahim Heydari (Journal of Global Entrepreneurship Research, 2019)
This longitudinal qualitative study aimed at investigating and analyzing rural entrepreneurship in the era of globalization. The main goal of this paper is to form and present a theoretical alternative for mainstream economic rural entrepreneurship. For this purpose, 40 entrepreneurs, experts, and practitioners in the agricultural and rural sector were specifically selected and textual data analysis was done by content analysis method using a strategy of theoretical coding (open and axial). The interviews have been done in two time periods from 2015 to 2018 in four Iran provinces. The results show that it is possible to separate four distinct types of rural entrepreneurship in Iran: (1) the orthodox globalized economic rural entrepreneurship, which is based on the productivist approach and economic development in agriculture; (2) the globalized technological rural entrepreneurship with the aim of the commercialization of agriculture through heavy using of technology; (3) the globalized applied scientific rural entrepreneurship with the emphasis on the applied literature in the history of development; and finally (4) the (rural) entrepreneurship as a supplementary of (rural) development, which tries to go beyond the dichotomies like rural-urban, and the mainstream entrepreneurialism. The main suggestion of the research is the so-called 'Anti-globalized Cultural Rural Entrepreneurship' that is a constructed rural entrepreneurship, and actually a process aiming to shift and transform the rural entrepreneurship discourse to the multifunctional agriculture and social movement domain.
Keywords: R0; 650; Rural development; Globalization; Rural entrepreneurship; Social constructionism; Content analysis; Iran